Genome evolution in the allotetraploid frog Xenopus laevis - Session, Adam M.; Uno, Yoshinobu; Kwon, Taejoon; Chapman, Jarrod A.; Toyoda, Atsushi; Takahashi, Shuji; Fukui, Akimasa; Hikosaka, Akira; Suzuki, Atsushi; Kondo, Mariko; van Heeringen, Simon J.; Quigley, Ian; et al. (Nature (London), 2016)
To explore the origins and consequences of tetraploidy in the African clawed frog, we sequenced the Xenopus laevis genome and compared it to the related diploid X. tropicalis genome. We characterize the allotetraploid origin of X. laevis by partitioning its genome into two homoeologous subgenomes, marked by distinct families of ‘fossil’ transposable elements. On the basis of the activity of these elements and the age of hundreds of unitary pseudogenes, we estimate that the two diploid progenitor species diverged around 34 million years ago (Ma) and combined to form an allotetraploid around 17–18 Ma. More than 56% of all genes were retained in two homoeologous copies. Protein function, gene expression, and the amount of conserved flanking sequence all correlate with retention rates. The subgenomes have evolved asymmetrically, with one chromosome set more often preserving the ancestral state and the other experiencing more gene loss, deletion, rearrangement, and reduced gene expression. The two homoeologous subgenomes in the allotetraploid frog Xenopus laevis evolved asymmetrically; one often retained the ancestral state, whereas the other experienced gene loss, deletion, rearrangement and reduced gene expression. Genomic evolution in Xenopus laevis Xenopus laevis , also known as the African clawed frog or platanna, is an important model organism that is used in the study of vertebrate cell and developmental biology. It is a palaeotetraploid—the product of genome duplications that occurred many millions of years ago. This makes X. laevis ideal for the study of polyploidy, but has greatly complicated genome sequencing. Here an international research collaboration reports the X. laevis genome sequence and compares it to that of the related X. tropicalis . Their analyses confirm that X. laevis is an allotetraploid and distinguishes two subgenomes that evolved asymmetrically—one often retained the ancestral state and the other was subject to gene loss, deletion, rearrangement and reduced expression. The two diploid progenitor species diverged about 34 million years ago, combining to form an allotetraploid about 18 million years ago.